Nonreciprocal photonic surface states in periodic structures of magnetized plasma nanospheres - A. Christofi; N. Stefanou (Physical Review B, 2013)
We report on the occurrence and properties of photonic surface states in periodic structures of magnetized plasma nanospheres by means of rigorous calculations using the full-electrodynamic layer-multiple-scattering method, properly extended to treat gyrotropic spheres with arbitrarily oriented gyration vector. More specifically, dispersion diagrams of Tamm states at the (001) surface of a semi-infinite fcc crystal of plasma nanospheres and of guided modes of a square array of such spheres supported by a quartz substrate, without and under the action of an in-plane static uniform magnetic field, are analyzed and nonreciprocal optical response, which emerges as a result of the simultaneous lack of space-inversion and time-reversal symmetries, is demonstrated in the Voigt geometry.